EKSISTENSI IRIGASI SEMI TEKNIS TERHADAP USAHATANI PADI SAWAH (Oryza sativa L.) DI DESA PAGAR JATI KECAMATAN KIKIM SELATAN KABUPATEN LAHAT - Sandela, Yussi; Sobri, Khaidir (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2019)
ABSTRACT This study aims to determine the development of rural irrigation in Pagar Jati Village, to determine the technical production in semi-technical irrigated land in Pagar Jati Village and to find out how much income for rice farming in Pagar Jati Village. This research has conducted in Pagar Jati Village, South Kikim District, Lahat Regency, from February to April 2019. The sampling method used was Purposive sampling and Simple random sampling with farmer respondents who planted rice farming using irrigation in Pagar Jati Village. Data collection techniques used in this study are observation and interviews directly with respondents using a tool in the form of a questionnaire or a list of questions that have been prepare in advance. The data analysis method used is descriptive qualitative and quantitative descriptive analysis. The results of the study revealed that Irrigation in the Pagar Jati Village made in 1971 with rural irrigation, semi-technical irrigation made in early 1983 during the leadership of Mr. Saini, this based on flash floods that occurred in 1979. Current irrigation building conditions are still functioning, but there is already a broken part because from construction in 1983 until 2018, it has never been repairing. And then, on March 21, 2019, the South Sumatra Provincial Government held a meeting at the Pagar Jati Village Office to discuss the improvement of irrigation buildings in the village and the plan implemented on March 24, 2019. Then the production techniques carried out by farmers in Pagar Jati Village, in general, have followed the advice. Except, inland processing activities, especially in leveling activities, there were five people (15%) who did not do land leveling, and in the use of fertilizer. For example, there were 17 people (52%) who had not followed recommendations from the provincial government. And the income earned by example farmers in 2018 in Pagar Jati Village averaged Rp 20,813,752.60 /lg/MT.